2013
DOI: 10.1371/journal.pone.0053834
|View full text |Cite|
|
Sign up to set email alerts
|

Tim-3 Expression in Cervical Cancer Promotes Tumor Metastasis

Abstract: BackgroundT cell immunoglobulin mucin-3 (Tim-3) has been identified as a negative regulator of anti-tumor immunity. Recent studies highlight the important role of Tim-3 in the CD8+ T cell exhaustion that takes place in both human and animal cancer models. However, the nature of Tim-3 expression in the tumor cell and the mechanism by which it inhibits anti-tumor immunity are unclear. This present study aims to determine Tim-3 is expressed in cervical cancer cells and to evaluate the role of Tim-3 in cervical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
122
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 18 publications
10
122
1
2
Order By: Relevance
“…Recent studies reported the ectopic expression of TIM-3 in lineages other than hematopoietic cells, particularly in primary cancer cells, including melanoma [52], non-small cell lung cancer [53], cervical cancer [54] and liposarcoma [55]. Importantly, patients with TIM-3 positive cancer cells had a significantly shorter survival time than those with TIM-3 negative cancer cells in non-small cell lung cancer [53] and cervical cancer [54].…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported the ectopic expression of TIM-3 in lineages other than hematopoietic cells, particularly in primary cancer cells, including melanoma [52], non-small cell lung cancer [53], cervical cancer [54] and liposarcoma [55]. Importantly, patients with TIM-3 positive cancer cells had a significantly shorter survival time than those with TIM-3 negative cancer cells in non-small cell lung cancer [53] and cervical cancer [54].…”
Section: Perspectivementioning
confidence: 99%
“…Importantly, patients with TIM-3 positive cancer cells had a significantly shorter survival time than those with TIM-3 negative cancer cells in non-small cell lung cancer [53] and cervical cancer [54]. TIM-3 expression in these various types of malignant cells raises the possibility of tumorigenic function of TIM-3.…”
Section: Perspectivementioning
confidence: 99%
“…Jajosky et al also pointed out that, RepSox (a reprogramming tool and inhibitor of transforming growth factor-b receptor 1) accelerated loss of Tim-3 from the surface of AML cells by inhibiting TGF-b signaling. 34 Tim-3 as human cancer prognostic factor The expression of TIM-3 on T cells was poor clinic pathological parameters such as nodal metastasis and advanced cancer stages in gastric cancer, 35 lung cancer, 36 cervical cancer 37 and ovarian cancer. 38 The ectopic expression of TIM-3 in tumor cells has been suggested as a potential, independent prognostic factor for patients with lung cancer, 36 cervical cancer 37 and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…34 Tim-3 as human cancer prognostic factor The expression of TIM-3 on T cells was poor clinic pathological parameters such as nodal metastasis and advanced cancer stages in gastric cancer, 35 lung cancer, 36 cervical cancer 37 and ovarian cancer. 38 The ectopic expression of TIM-3 in tumor cells has been suggested as a potential, independent prognostic factor for patients with lung cancer, 36 cervical cancer 37 and prostate cancer. 39 The Tim-3/galectin-9 signaling pathway mediates Tcell senescence was also involved in patients with hepatitis B virus (HBV)-associated HCC, thus it has been a potential immunotherapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…TiM-3 belongs to the TiM family and was initially observed selectively expressed on terminally differentiated interferon g-producing CD4  T helper type 1 (Th1) cells and CD8  cytotoxic T cells [64,65], as well as on Th17, DCs, monocytes, Tregs, mast cells, nK cells, TiLs, also on tumor cells, such as melanoma, SCC, gastric cancer and nSCLC cells, but indeed not on CD4  T helper type 1 (Th2) cells [65][66][67][68][69][70][71][72][73].…”
Section: Expression and Inhibitory Role In Immune Response Of Tim-3mentioning
confidence: 99%